Analisis Kualitatif Efektivitas Implementasi Proyek Penguatan Profil Pelajar Pancasila dalam Membentuk Karakter Gotong Royong Siswa di SMP Negeri 4 Medan - Dewi Hartika; Siagian, Liber (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effectiveness of the implementation of the Strengthening the Pancasila Student Profile Project (P5) in shaping the spirit of mutual cooperation among students at SMP Negeri 4 Medan for the 2024/2025 academic year. This study employs a descriptive qualitative approach that focuses on data collection and analysis through observation, interviews, and documentation. The research was conducted due to the challenges in implementing the Merdeka Curriculum, particularly in fostering the character of mutual cooperation among students. Using non-probability sampling techniques and quota sampling methods, this research involves teachers, students, and school stakeholders as research subjects. The results of the study indicate that the implementation of P5 significantly shapes the character of mutual cooperation among students. Students demonstrate improvements in social skills, empathy, and collaborative abilities through various activities designed within the project. Activities such as social service and collaborative projects successfully create a positive atmosphere in the school, where students appreciate each other and work together to achieve common goals. Additionally, students also show an increase in their sense of responsibility in decision-making.